Linguistic and emotional dynamics in satirical vs. real news: a psycholinguistic analysis - Wick-Pedro, Gabriela; Santos, Roney Lira de Sales; Vale, Oto (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2024: Anais do XV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2024.245398, 2024)
This study compares the psycholinguistic differences between satirical and real news using data from LIWC (Linguistic Inquiry and Word Count). We found that satirical news utilizes a broader range of emotional and rhetorical resources, often exaggerating or subverting reality, while real news maintains a more factual and objective tone. This highlights the critical and humorous role of satire in social communication. Furthermore, the research advances the field of NLP by improving satire detection through a psycholinguistic lens, contributing to the development of algorithms that effectively differentiate satirical news from fake news and help combat misinformation.